A Rare Case with Recurrent Abdominal Pain as the First Symptom: AL Amyloidosis with Colon Involvement Combined with Pulmonary Adenocarcinoma - Wei J; Hu Y; Lu C; Hu M; Wang Q (Journal of Inflammation Research)
Jiaojiao Wei, Yibing Hu, Chong Lu, Minli Hu, Qunying Wang Department of Gastroenterology, Affiliated Jinhua Hospital, Zhejiang University School of Medicine, Jinhua, Zhejiang, People’s Republic of ChinaCorrespondence: Qunying Wang, Department of Gastroenterology, Affiliated Jinhua Hospital, Zhejiang University School of Medicine, Jinhua, Zhejiang, People’s Republic of China, Email wqy616717@126.comBackground: Amyloidosis combined with lung cancer is a rare occurrence. To date, there are no reported cases of amyloid light-chain(AL) amyloidosis solely affecting the colon combined with pulmonary adenocarcinoma.Case Summary: Here, we describe a case of a 66-year-old woman who presented with recurrent abdominal pain and was eventually diagnosed with AL amyloidosis with colon involvement and pulmonary adenocarcinoma. We also review the relevant literature and discuss the relationship between amyloidosis and lung malignancies. Significantly, lung cancer may contribute to the deposition of amyloid through paraneoplastic mechanisms. And in published case reports, the pathological type of lung cancer associated with AL amyloidosis was all adenocarcinoma.Conclusion: Such cases are rare but provide new insights into the relationship between amyloidosis and lung malignancies. The mechanism of amyloid protein deposition in relation to lung cancer or malignancies remains unknown, further research in this field is warranted.Keywords: amyloidosis, adenocarcinoma, lung cancer, comorbidity